Floorball goaltending movements during a game: A quantitative observational study - Tengman, E.; Pettersson, A.; Jönsson, L.; Tervo, T. (BMC Sports Science, Medicine and Rehabilitation, 2025)
Background More knowledge about floorball goalkeepers` game movements and biomechanical demands is warranted. Therefore, the aim of this study was to observe type and frequency of female floorball goalkeepers` movements during a game.